A rapid separation of two distinct populations of mouse corneal epithelial cells with limbal stem cell characteristics by centrifugation on percoll gradient - Krulová, Magdaléna; Pokorná, Kateřina; Lenčová, Anna; Frič, Jan; Zajícová, Alena; Filipec, Martin; Forrester, John V; Holáň, Vladimír (Investigative ophthalmology & visual science, 2008)
PURPOSE: To detect and isolate cells with stem cell (SC) characteristics in the limbus of the mouse. METHODS: Limbal tissues from BALB/c mice were trypsin-dissociated and separated on the gradient Percoll (Fluka, Buchs, Switzerland). Several fractions were isolated and characterized by real-time PCR for the presence of limbal SC markers and differentiation markers of corneal epithelial cells by flow cytometry for the determination of the side-population (SP) phenotype and growth properties in vitro. RESULTS: Cells retained in the lightest fraction (40% Percoll) and in the densest fraction (80% Percoll) of the gradient were both enriched for populations with a high expression of the SC markers ABCG2 and Lgr5 and also expressing the SP phenotype. However, the lightest fraction (representing approximately 12% of total limbal cells) contained cells with the strongest spontaneous proliferative capacity and expressed the corneal epithelial differentiation marker K12. In contrast the densest fraction (<7% of original cells) was K12 negative and contained small nonspontaneously proliferating cells, which instead were positive for p63. Unexpectedly, cells from this fraction had the highest proliferative activity when cultured on a 3T3 feeder cell monolayer. CONCLUSIONS: These findings demonstrate the presence of two distinct populations of corneal epithelial cells with limbal SC characteristics, based on differential expression of the keratin-specific marker K12 and transcription factor p63, and suggest a difference in developmental stage of the two populations, with the K12(-)p63(+) population being closer to the primitive limbal SC
Keywords: financování organizované; buněčné dělení; ATP-Binding Cassette Transporters; Animals; Povidone; 3T3 Cells; Silicon Dioxide; Female; Stem Cells; polymerázová řetězová reakce; průtoková cytometrie; Polymerase Chain Reaction; ženské pohlaví; Fibroblasts; Centrifugation, Density Gradient; ABC transportéry; Mice; povidon; Flow Cytometry; kmenové buňky; fibroblasty; Mice, Inbred BALB C; myši; Financing, Organized; separace buněk; Male; myši inbrední BALB C; buňky 3T3; rohovkový epitel; oxid křemičitý; Cell Separation; centrifugace - gradient hustoty; Epithelium, Corneal; zvířata; mužské pohlaví; Cell Division